Arf1 and ARFGEF2/Sec71 control neuroblast polarity by anchoring nonmuscle myosin II - Mahekta R. Gujar; Ye Sing Tan; Yang Gao; Hongyan Wang (Proceedings of the National Academy of Sciences, 2025)
Neural stem cells (NSCs) can self-renew and undergo differentiation via asymmetric division. Dysregulation in the balance between self-renewal and differentiation can lead to tumor formation or neurodevelopmental disorders. However, the regulation of phosphatidylinositol transfer protein (PITP)-dependent PI(4)P pools and myosin localization during asymmetric division in dividing cells is not well established. Here, we show that the Golgi proteins Arf1 and ARFGEF2/Sec71 control asymmetric division of Drosophila NSCs by facilitating the localization of myosin II regulatory light chain, Sqh, to the NSC cortex. Arf1 can physically associate with Sqh and Vibrator, a type I PITP that stimulates phospholipid PI4K activity for PI(4)P production. Further, Arf1 and Sec71 facilitate PI(4)P localization to the cell cortex of neuroblasts. Our data provide evidence that the Golgi proteins Arf1 and its GEF Sec71 facilitate neuroblast polarity through phospholipid-dependent nonmuscle myosin II cortical localization.